PENERAPAN MODEL PROBLEM BASED LEARNING PADA MATERI PROGRAM LINEAR KELAS XI MAN 3 PONTIANAK - Saputra, Wahyu Dwi; Yani, Ahmad; Bistari, Bistari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to know and describe the teacher’s class management, student’s learning activities, student’s outcome in the implementation and student respond of Problem Based Learning model in the linear programming topic at class XI IPA MAN 3 Pontianak. The research method is quantitative method. The reseach subject is students in class XI IPA. Based on the data analysis that review four aspects, the result are: (1) the teacher’s class management categorized very good with average score 3,505; (2) student’s learning activities categorized active with average score 74,53%; (3) student’s outcome is not reaced classical completenes with only 15% of student can achieve the minimum completenes criteria; (4) studen’s respond categorized positive. Because only three out of four aspects that achieve, the conclusion of this research is the implementation of Problem Based Learning model less effective to apply in the linear programming topic at class XI IPA MAN 3 Pontianak. Keywords: Problem Based Learning model, effectiveness, linear programming topic